A new species of Aididae (Lepidoptera, Zygaenoidea) and the first record of the family for the Northern Region of Brazil - Lourido, Gilcélia Melo (EntomoBrasilis, 2021)
A new species of Aididae is described and illustrated based on adults (male and female) and immature (last instar larvae). The larvae were found infesting leaves of Inga edulis Martius (Fabaceae) in the municipality of Autazes, State of Amazonas, representing the first record of Aididae in the northern region of Brazil. The new species is further compared with its closest species, Aidos amanda (Stoll, 1782).